Antigenic relationship among isolates of Ascochyta rabiei and chickpea cultivars - and NEENA MITTER, G. UMA DEVI, MAHENDRA PAL (Indian Phytopathology, 2002)
Polyclonal antisera (titre 1:1024) were raised against antigens D11 (highly virulent) and ICK (least virulent), isolates of Ascochyta rabiei. Similarly, antisera were also raised against antigens of chickpea genotypes I-13 (resistant to Aschochyta blight) and Pusa 256 (susceptible to Aschochyta blight) (titre 1:2048). Cross-reactivity tests were carried out using ELISA and dot immunobinding assay (DIBA) techniques. The results indicate that A. rabiei isolates could be differentiated serologically into 2 groups. D11 and G2 were placed in 1 group and GL866, ICK and ICH in the other. The presence of common antigens between chickpea genotypes and A. rabiei isolates were determined by direct antigen coating-ELISA and also DIBA. The reaction of antiserum of the most virulent isolate D11 was stronger with antigens from Pusa 256 (susceptible) and I-13 (resistant) than the reaction of the least virulent isolate, ICK, with the 2 genotypes.